How to Avoid Plagiarism: Student Handbook - Gojná, Zuzana (Karolinum Press, 2021)
In this handbook you'll learn: - how to formulate your own ideas - how to correctly reference different sources - what exactly constitutes plagiarism - how to avoid various forms of plagiarism - examples of (in)famous cases of plagiarism - three tips against plagiarism - and finally, some advice for avoiding time pressure.